Efforts to Increase Creativity in Early Children Through Picture Story Media - Susan Risanti Kurniatin; Rita Aryani (Eduvest - Journal of Universal Studies, 2021)
The condition of creativity in PGRI Margajaya Kindergarten, Mangunreja District is still low, children cannot concentrate through illustrated stories, children are not interested in listening to illustrated stories, plus teachers do not use learning media in order to attract the attention of students. High creativity encourages children to learn and work more so that one day they can create new things beyond our expectations. Storytelling has a positive impact on the development of creativity. Children are accustomed to concentrating on a topic, dare to develop their creations, organize themselves/self-confidence, stimulate children to think imaginatively, and increase their new vocabulary. To realize this desire, the authors carried out Classroom Action Research (CAR) which consisted of two cycles and in the process was assisted by the principal as well as a companion class teacher. The results of this study indicate that there is an increase in children's creativity through picture stories, namely pre-cycle creativity by 20%, increasing creativity in cycle I by 45% and increasing creativity in cycle II reaching 85%. Based on the results of the study, it can be concluded that illustrated stories can increase the creativity of children's work in PGRI Margajaya Kindergarten, Mangunreja District.